On three facts of reticences in the classical mathematical modeling of elastic materials - Rushchitsky, J. J. (Publishing House of Lviv Polytechnic National University, 2014)
Three facts of reticences (passing over in silence, an absence of comments) in the procedures of mathematical modeling of elastic materials are described and commented. The first fact consists in a reticence of one of the first steps in the mentioned above procedure an assumption that the kinematics of deformation is described by the linear approximation of motion of material continuum, namely by gradients of deformation. In the paper, a novel nonlinear approach to this procedure is offered. The second and third facts are associated with constitutive relations. The second fact consists in the absence of necessary comments relative to determination of smallness of strains and gradients of displacements (absence of comments relative to a criterion of applicability of the linear model) because the criterion |ui,k| ≪ 1 is sufficiently abstract. It is shown that there exists a based on the nonlinear Cauchy relations approximate procedure of determination of threshold values of strains and gradients of deformations starting with which a nonlinearity of process appears. The third fact consists in the absence of comments relative to essential differences between the nonlinear constitutive equations, which are written for the ordered pairs “Lagrange stress tensor – Cauchy-Green strain tensor” and “Kirchhoff stress tensor – gradients of displacements”. It is shown on an example of the shear stress and the Murnaghan model of nonlinear elastic deformation that deviation from the corresponding straight lines of linear deformation for different pairs differs in many times in the range of small strains and small gradients of displacements. The general estimate of facts of reticences looks positive, because for one part of scientists-mechanicians the reticences form the comfort feeling of monolithic character of the classical theory of elasticity, whereas for another part the reticences form a space for development of the theory of elasticity. Описано i прокоментовано три факти умовчання (вiдсутностi коментарiв) в процедурах математичного моделювання пружних матерiалiв. Перший факт полягає в некоментуваннi одного з перших крокiв у згаданiй процедурi припущення, що кiнематика деформування описується за допомогою лiнiйної апроксимацiї руху матерiального континууму, а саме за допомогою градiєнтiв деформацiї. У статтi запропоновано певний новий нелiнiйний пiдхiд в процедурi. Другий i третiй факти пов’язанi з побудовою визначальних рiвнянь. Другий факт полягає у вiдсутностi належних коментарiв щодо визначення малостi деформацiй i градiєнтiв змiщень (вiдсутностi коментарiв щодо критерiю застосування лiнiйної моделi, оскiльки критерiй |ui,k| ≪ 1 є досить абстрактним). Показано, що iснує базована на нелiнiйних спiввiдношеннях Кошi наближена процедура визначення порогових значень деформацiй i градiєнтiв змiщень, при яких вже починає виявлятися нелiнiйнiсть процесу деформування. Третiй факт полягає у вiдсутностi коментарiв щодо суттєвих вiдмiнностей мiж нелiнiйними визначальними рiвняннями, записаними для впорядкованих пар ¾тензор напружень Лягранжа – тензор деформацiй Кошi-Грiна¿ та ¾тензор напружень Кiрхгоффа – градiєнти змiщень¿. Показано на прикладi зсувних напружень та моделi нелiнiйного пружного деформуванняМернагана, що вiдхилення вiд вiдповiдних прямих лiнiйного деформування для рiзних пар вiдрiзняються в дiапазонi малих деформацiй i малих градiєнтiв змiщень у багато разiв. Загальна оцiнка фактiв умовчання виглядає позитивною, оскiльки для однiєї частини вчених-механiкiв умовчання створює комфортне вiдчуття монолiтностi класичної теорiї пружностi, а для iншої частини умовчання створюють простiр для розвитку теорiї.
Про три факти умовчання в класичному математичному моделюваннi пружних матерiалiв
Keywords: mathematical modeling of elastic materials; reticences in classical nonlinear theory of elasticity; smallness of strains and gradients of displacements; nonlinear kinematic parameters; математичне моделювання пружних матерiалiв; замовчування в класичнiй теорiї пружностi; малiсть деформацiй i градiєнтiв змiщень; нелiнiйнi кiнематичнi параметри